2017
DOI: 10.1038/gene.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis for variation in plasma IL-18 levels in persons with chronic hepatitis C virus and human immunodeficiency virus-1 infections

Abstract: Inflammasomes are multi-protein complexes integrating pathogen-triggered signaling leading to the generation of pro-inflammatory cytokines, including interleukin-18 (IL-18). Hepatitis C virus (HCV) and human immunodeficiency virus-1 (HIV) infections are associated with elevated IL-18, suggesting inflammasome activation. However, there is marked person-to-person variation in the inflammasome response to HCV and HIV. We hypothesized that host genetics may explain this variation. To test this, we analyzed the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…This issue is complicated with considerable information regarding the association of the polymorphisms within the inflammasomes related molecules with chronic viral hepatitis and their complications. Vergara et al, showed that IL-18 gene polymorphisms are associated with altered serum levels of the cytokine in the HCV infected patients [91]. Association of IL-18 promoter genotype -137 G/G and allele -137 G with decreased serum levels of the cytokine and chronic HBV infectivity, respectively, has been reported by Jiang and colleagues [92].…”
Section: Inflammasomes; the Crucial Inducers Of Chronic Inflammation mentioning
confidence: 85%
“…This issue is complicated with considerable information regarding the association of the polymorphisms within the inflammasomes related molecules with chronic viral hepatitis and their complications. Vergara et al, showed that IL-18 gene polymorphisms are associated with altered serum levels of the cytokine in the HCV infected patients [91]. Association of IL-18 promoter genotype -137 G/G and allele -137 G with decreased serum levels of the cytokine and chronic HBV infectivity, respectively, has been reported by Jiang and colleagues [92].…”
Section: Inflammasomes; the Crucial Inducers Of Chronic Inflammation mentioning
confidence: 85%
“…IL-18 and IL-1β are important factors contributing to the development of chronic hepatocellular inflammation [11,21,34,35]. Considering that, inflammasome activation is the only described mechanism to convert pro-IL-18 to mature IL-18 [15,19]. So, we focused in our study on IL-18 concentration being a marker of liver inflammation that induced mainly from inflammasomes assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasomes are intracellular innate immune sensors, including: NLRP3, AIM2 and IFI16 [14]. They are multi-protein cytosolic complexes that integrate several pathogens triggered signaling cascades, ultimately leading to caspase-1 activation and secretion of pro-inflammatory cytokines including IL-18 and IL-1β [15]. Although, multiple types of inflammasomes were reported to be involved in HCV, others are still unknown and need further investigations [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations